Development of lentiviral vectors for efficient glutamatergic-selective gene expression in cultured hippocampal neurons. Issue 1 (December 2018) - Egashira, Yoshihiro; Mori, Yasunori; Yanagawa, Yuchio; Takamori, Shigeo
Abstract Targeting gene expression to a particular subset of neurons helps study the cellular function of the nervous system. Although neuron-specific promoters, such as the synapsin I promoter and the α-CaMKII promoter, are known to exhibit selectivity for excitatory glutamatergic neuronsin vivo, the cell type-specificity of these promoters has not been thoroughly tested in culture preparations. Here, by using hippocampal culture preparation from theVGAT-Venus transgenic mice, we examined the ability of five putative promoter sequences of glutamatergic-selective markers including synapsin I, α-CaMKII, the vesicular glutamate transporter 1 (VGLUT1), Dock10 and Prox1. Among these, a genomic fragment containing a 2.1 kb segment upstream of the translation start site (TSS) of theVGLUT1 implemented in a lentiviral vector with the Tet-Off inducible system achieved the highest preferential gene expression in glutamatergic neurons. Analysis of various lengths of the VGLUT1 promoter regions identified a segment between −2.1 kb and −1.4 kb from the TSS as a responsible element for the glutamatergic selectivity. Consistently, expression of channelrhodopsin under this promoter sequence allowed for selective light-evoked activation of excitatory neurons. Thus, the lentiviral system carrying the VGLUT1 promoter fragment can be used to effectively target exogenous gene expression to excitatory glutamatergic neurons in cultures.